Life-history traits of the Threatened Freshwater Fish Cirrhinus reba (Hamilton 1822) (Cypriniformes: Cyprinidae) in the Ganges River, Northwestern Bangladesh - Hossain, Md. Yeamin; Khatun, MST. Monira; Jasmine, Saleha; Rahman, Md. Mosaddequr; Jahan, Sharmin; Sayed Jewel, Md. Abu; Ohtomi, Jun (Universiti Kebangsaan Malaysia, 2013)
The threatened Reba carp, Cirrhinus reba is a freshwater fish species found in ponds, rivers, canals and tanks of Bangladesh, India, Myanmar, Nepal and Pakistan. The present study describes the first complete and inclusive description of life-history traits including sex ratio, length-frequency distributions (LFD), length-weight relationships (LWR), condition factors (Allometric, KA; Fulton’s, KF; Relative condition, KR; Relative weight, WR), form factor (a3.0) and size at first sexual maturity of C. reba in the Ganges River, NW Bangladesh. Sampling was done using traditional fishing gears including cast net, square lift net and conical trap from April 2011 to March 2012. The total length (TL), fork length (FL) and standard length (SL) were measured to the nearest 0.01 cm using digital slide calipers and total body weight (BW) was measured using an electronic balance with 0.01 g accuracy. The LWR was calculated using the expression: W= a Lb, where W is the BW, L the TL. The size at first sexual maturity of C. reba was estimated using the empirical equation by Binohlan and Froese (2009) for male and female, separately. A total of 250 specimens ranging from 8.00 cm – 23.40 cm TL and 4.30 g – 200 g BW were analyzed in this study. The overall sex ratio did not differ significantly from the expected value of 1:1 (χ2 = 3.38, p< 0.05), but there was significant differences in the TL-frequency distributions (Mann-Whitney U-test, p< 0.001) between male (median = 12.00 cm) and female (median = 15.80 cm). The calculated b for the LWR indicated positive allometric growth (> 3.00) in male and female and there was significant differences in the intercepts (ancova, p< 0.001) and in the slopes (ancova, p< 0.001) between the sexes. In addition, the Mann-Whitney U-test showed significant differences in the Fulton’s condition factor between male and female (p< 0.001). The one sample t-test showed that the mean WR (actual mean = 99.50) did not differ from 100 for male (p= 0.523) and female (p= 0.197) in this study, indicating the habitat was still in good condition for C. reba. Moreover, the size at sexual maturity of male and female C. reba were estimated as 11.50 cm TL and 13.50 cm TL, respectively. The results of this study would be useful for the sustainable conservation of this threatened carp fishery in Bangladesh and also neighboring countries.